"Nothing's available": Young fathers' experiences with unmet information needs and barriers to resolving them. Issue 2 (March 2020) - Mniszak, C.; O'Brien, H.L.; Greyson, D.; Chabot, C.; Shoveller, J.
Highlights: Young fathers often have unexpressed and unaddressed information needs. Information inequality for young fathers was influenced by gender several levels. Young fathers encounter barriers when accessing parenting services. Young mothers often serve as information intermediaries for young fathers. Young fathers avoid asking for support to adhere to traditional masculine values. Abstract: Young fathers, like all parents, have a range of information needs, such as learning how to introduce their babies to solid foods. Yet compared to young mothers and older parents, they have fewer resources available to them. To date, young fathers have not been identified as a priority population in need of parenting-related information and face unequal access to information resources. This inequality is in part related to gender stereotypes and social biases about young men who become parents at "too early" an age. Through interviews and field observation conducted during a longitudinal ethnographic study of young mothers, fathers, their parents, and service providers in two cities in British Columbia, Canada, we examined young fathers' gendered experiences accessing parenting information and resources. Using an ecological model of information needs, we identified factors at different levels: micro (e.g., personal), meso (e.g., relational) and macro (e.g., access to city/provincial parenting programs and resources) that revealed information inequalities for young fathers. Our findings illustrate that young fathers often have unexpressed and unaddressed information needs due to barriers they encounter when accessing services, the stigma they experience as early age parents, and social pressures that result in avoiding asking for help in order to adhere to traditional masculine values.